If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -8m = -5m + 16 Reorder the terms: 1 + -8m = 16 + -5m Solving 1 + -8m = 16 + -5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5m' to each side of the equation. 1 + -8m + 5m = 16 + -5m + 5m Combine like terms: -8m + 5m = -3m 1 + -3m = 16 + -5m + 5m Combine like terms: -5m + 5m = 0 1 + -3m = 16 + 0 1 + -3m = 16 Add '-1' to each side of the equation. 1 + -1 + -3m = 16 + -1 Combine like terms: 1 + -1 = 0 0 + -3m = 16 + -1 -3m = 16 + -1 Combine like terms: 16 + -1 = 15 -3m = 15 Divide each side by '-3'. m = -5 Simplifying m = -5
| 8a-4-4a=6-a | | 3x-11=30 | | x/2+2/3=3/4 | | v=x(25-2x)(12-2x) | | 7p-5(3+p)=7p-15-5p | | -16=4a+2a | | 16.7d+66.7=25d+-.5 | | .666(5)= | | 3.5s-7.3=-7.3+2.6s | | (2x-11)/3=4+x | | x+7/2=7 | | -8x-16=-8(2x-6) | | -16=14a+2a | | 16n+1=80 | | 5-(3-f)-5=6(3-f) | | (5x/2)=3x+5 | | (2x-11)/3=4/3+x | | 22/11x9-3^2 | | 5y=-6(0)-30 | | (x+2)/(x-3)=2 | | v=x(18-2x)(9-2x) | | 4x=-2(2x+4) | | x^2+8x+12y+4=0 | | (7xy)-(3xy)= | | 6m+7m=0 | | x(3x^2-5x-2)=0 | | 8+x=-31 | | 6(v+3)-2v=2(2v+3)-14 | | -3=-1/3h-10 | | 2/3x-12 | | 3-(x-4)=48 | | 18=x+3+2x |